Prevedba plač javnih uslužbencev pred sodiščem - Pustovrh Pirnat, Tanja (Delavci in delodajalci, 2012)
The author deals with the question of the conversation of wages of public employees after the implementation of the new salary system in the slovenian public sector. She introduces the legal framework and recent judicial practice. A special attention is given to the question of the access to judicial protection before labour courts.
Keywords: javni sektor; javni uslužbenci; plače; plačni sistemi; pravna ureditev; zaposleni